Service Learning in Croatia and the region: progress, obstacles and solutions - Mikelić Preradović, Nives (2011)
The goal of the paper is to discuss the possibilities of transforming universities in Croatia and the region into places that take account of the emerging community trends and current challenges that our students should be capable of dealing with once they finish their studies. Service learning (SL) was introduced in the largest faculty of the University of Zagreb (Faculty of Humanities and Social Sciences) in 2006-07 through a series of faculty workshops and through academic courses. The goals and requirements of this teaching and learning method were based upon our U.S. experience, gained at the George Washington University. Since then around 50 SL projects in the IT field have been completed and evaluated. Service learning was also introduced in the Faculty of Economy at the University of Rijeka in 2008. In 2009 it was added as a regulation of the Croatian National Youth program 2009-2013, approved by the Croatian Government. Also, in the same year the Croatian translation of the term “service learning” (“drustveno korisno ucenje”) offered by the author of this paper became accepted as a common term at the JFDP (Junior Faculty Development Program) Regional Conference. Although the workshops were extremely popular both in Croatia and the region, and although SL courses achieved remarkable student enrollment in a short time, the number of faculty who have so far implemented it as a teaching strategy is very low. This paper discusses the reasons for faculty resistance to engage in SL and some possible solutions.
Projekt MZOS
Projekt MZOS
ENG